A carbon-isotope perturbation at the Pliensbachian-Toarcian boundary: evidence from the Lias Group, NE England - Littler, K; Hesselbo, S; Jenkyns, H (2010)
A perturbation in the carbon-isotope record at the time of the Pliensbachian-Toarcian boundary (∼184 Ma) in the Early Jurassic is reported, based on new data from Yorkshire, England. Two sharp δ13C org negative excursions, each with a magnitude of ∼ -2.5‰ and reaching minimum values of -28.5‰ , are recorded in the bulk organic-matter record in sediments of latest Pliensbachian to earliest Toarcian age. A similar pattern of negative carbon-isotope excursions has been observed at the stage boundary in the SW European section at Peniche, Portugal in δ13Ccarbonate, δ13Cwood and δ13Cbrachiopod records. The isotopic excursion is of interest when considering the genesis and development of the later Toarcian Oceanic Anoxic Event (OAE), as well as the second-order global extinction event that spans the stage boundary. Furthermore, the isotope excursion potentially provides a chemostratigraphic marker for recognition of the stage boundary, which is currently achieved on the basis of different ammonite faunas in the NW European and Tethyan realms. Copyright © Cambridge University Press 2009.